2012
DOI: 10.1159/000337032
|View full text |Cite
|
Sign up to set email alerts
|

Proxy Indicators for Identifying Iron Deficiency among Anemic Vegetarians in an Area Prevalent for Thalassemia and Hemoglobinopathies

Abstract: Background and Aims: The study aimed to determine the proportion of iron deficiency (ID) anemia (IDA) among vegans in northeast Thailand and to explore whether mathematical formulas derived from red blood cell (RBC) indices are applicable for IDA screening in the study population. Methods: Blood samples from 234 individuals (age 6–45 years) living in a vegan community were taken. Complete blood cell count, serum ferritin, hemoglobin profiles and DNA analysis for α-thalassemia were determined. Anemia was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
(39 reference statements)
1
15
0
2
Order By: Relevance
“…Nonetheless, food consumption behaviour, which differs from region to region, may also account for the difference in anemia prevalence. Of note, the high prevalence and complexity of thalassemia Including homozygous α + -thalassemia, homozygous Hb CS, α 0 -thalassemia trait, and β-thalassemia trait *For anaemia, adjusted for length of menstruation and blood donation in recent 3 months; For ID, adjusted for BMI and length of menstruation observed in our study, which was very similar to that were reported in previous studies on adolescent, pregnant women, and vegetarians community in northeast Thailand [14,16,31], thus indicating the presence of heterogeneity of thalassemia and hemoglobinopathies in the region.…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, food consumption behaviour, which differs from region to region, may also account for the difference in anemia prevalence. Of note, the high prevalence and complexity of thalassemia Including homozygous α + -thalassemia, homozygous Hb CS, α 0 -thalassemia trait, and β-thalassemia trait *For anaemia, adjusted for length of menstruation and blood donation in recent 3 months; For ID, adjusted for BMI and length of menstruation observed in our study, which was very similar to that were reported in previous studies on adolescent, pregnant women, and vegetarians community in northeast Thailand [14,16,31], thus indicating the presence of heterogeneity of thalassemia and hemoglobinopathies in the region.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, the reference ranges of Hb and RBC counts between male and female are nearly similar, moreover, those of MCV, MCH, MCHC and RDW are the same (24). Both b-thal and iron deficiency are the major causes of anemia in all age groups of the Thai population (25)(26)(27)(28)(29)(30). Although, the b-thal Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators included also subjects with other types of hemoglobinopathy, like HbE [116,117,125], HbOArab [126] and HbS, both sickle cell thalassemia and sickle cell disease [48,94]. Unfortunately the numbers reported are too small for making a solid conclusion as to the utility of the discriminant indices in these conditions.…”
Section: Thalassemia Typesmentioning
confidence: 99%